Thermochronometry unveils ancient thermal regimes in the NW Pampean Ranges, Argentina: From Mesozoic rifting to Miocene flat‐slab subduction. (30th July 2022) - Ezpeleta, Miguel; Parra, Mauricio; Collo, Gilda; Wunderlin, Cecilia; Borrego, Angeles G.; Sobel, Edward R.; Glodny, Johannes
Abstract: Reconstructing thermal histories in thrust belts is commonly used to infer the age and rates of thrusting and hence the driving mechanisms of orogenesis. In areas where ancient basins have been incorporated into the orogenic wedge, a quantitative reconstruction of the thermal history helps distinguish among potential mechanisms responsible for heating events. We present such a reconstruction for the Ischigualasto‐Villa Unión basin in the western Pampean Ranges of Argentina, where Triassic rifting and late Cretaceous‐Cenozoic retroarc foreland basin development has been widely documented, including Miocene flat‐slab subduction. We report results of organic and inorganic thermal indicators acquired along three stratigraphic sections, including vitrinite reflectance and X‐ray diffractometry in claystones and new thermochronological [(apatite fission‐track and apatite and zircon [U‐Th]/He)] analyses. Despite up to 5 km‐thick Cenozoic overburden and unlike previously thought, the thermal peak in the basin is not due to Cenozoic burial but occurred in the Triassic, associated with a high heat flow of up to 90 mWm −2 and <2 km of burial, which heated the base of the Triassic strata to ~160°C. Following exhumation, attested by the development of an unconformity between the Triassic and Late‐Cretaceous–Cenozoic sequences, Cenozoic re‐burial increased the temperature to ~110°C at the base of the Triassic section and only ~50°C 7 km upsection, suggesting a dramatic decrease in the thermal gradient. The onset of Cenozoic cooling occurred at ~10 −8  Ma, concomitant with sediment accumulation and thus preceding the latest Miocene onset of thrusting that has been independently documented by stratigraphic–cross‐cutting relationships. We argue that the onset of cooling is associated with lithospheric refrigeration following establishment of flat‐slab subduction, leading to the eastward displacement of the asthenospheric wedge beneath the South American plate. Our study places time and temperature constraints on flat‐slab cooling that calls for a careful interpretation of exhumation signals in thrustbelts inferred from thermochronology only. Abstract : Multi‐sample thermal models and 1D thermal modeling for the Ischigualasto‐Villa Union Basin. Our study exemplifies that peak heating (Triassic) and the onset of the cooling (earliest Late Miocene) cannot be directly associated with peak burial (Cenozoic) and the onset of thrust induced exhumation (younger than 5 Ma), as it is commonly done in thermochronologic studies in sub‐andean basins. Thermal signatures in this basin are decoupled from subsidence and exhumation signals and rather respond to changes in basal heat flow.